Preparation of spherical microparticles from biodegradable natural and synthetic polymers for their application in regenerative medicine - M. G. Gordienko; T. N. Somov; Y. S. Yusupova; N. I. Chupikova; N. V. Menshutina (Тонкие химические технологии)
We have studied methods for preparing biodegradable microparticles for regenerative medicine based on chitosan, polylactic acid, collagen and gelatin. The main methods of forming particles become emulsification, coacervation and gelation. These methods can achieve the necessary parameters of the product such as size, porosity and shape by varying process parameters such as temperature, stirring speed and the concentration of solutions. For drying the microparticles vacuum freeze drying was used, which allows to maintain the spherical shape of the particles after drying. The resulting microparticles were examined and photographed using a scanning electron microscope. To determine the cytotoxicity of the microparticles their cell growth and attachment were studied in vitro.